The Use of RIASEC for Career Planning Information for Junior High School Students - Rusnawati Ellis; Sawal Mahaly; Muhamad Fadli; Rezki Hariko; Abdul Jalil Tuasikal (CV. TOTUS TUUS, 2024)
Implementation of career guidance in SMEs requires supporting facilities so that the service objectives can be achieved effectively and efficiently. These facilities include not only physical infrastructure such as career guidance rooms and technology devices, but also resources such as reference materials and evaluation tools. Restricted facilities can hinder the process of optimum career planning for students. Availability of supporting facilities is essential in the implementation of career guidance in the middle school. The various stages in the implementation of the Pkm activities are: 1) Preparation, 2) Implementation, 3) Support, 4) Evaluation. As for the methods used to the goals of PKM are a) Lecture and class discussion; b) group discussion; c) questioning and answering. Results from the Pkm activities show that there are varying interests among the pupils in several professions. Polwan became the main choice with the number of fans reaching 13 (23.2%), followed by TNI as the second choice with 12 fans (21%). The doctor's profession ranks third with 8 fans (14.3%), while the police are in the fourth place with 7 fans (12.5%).